2017
DOI: 10.1007/s11249-017-0946-1
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of White Etching Cracks (WECs) in Rolling Contact Fatigue-Tested 100Cr6 Steel

Abstract: The formation of white etching cracks (WECs) in steel rolling element bearings can lead to the premature rolling contact fatigue (RCF) failure mode called white structure flaking. Driving mechanisms are still debated but are proposed to be combinations of mechanical, tribochemical and electrical effects. A number of studies have been conducted to record and map WECs in RCF-tested samples and bearings failed from the field. For the first time, this study uses serial sectioning metallography techniques on non-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…The control of hydrogen concentrations and trapping within the sample before measurement is a complicated task requiring proper sample extraction, delivery, and preparation procedures prior to hydrogen concentration measurements. The loss of hydrogen during sample transportation from the service environment to the measurement site can be reduced by storing the specimen in liquid nitrogen [19]. However, the problem of hydrogen loss in the course of TDS measurement preparation, namely during AVC pumping, has not been considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of hydrogen concentrations and trapping within the sample before measurement is a complicated task requiring proper sample extraction, delivery, and preparation procedures prior to hydrogen concentration measurements. The loss of hydrogen during sample transportation from the service environment to the measurement site can be reduced by storing the specimen in liquid nitrogen [19]. However, the problem of hydrogen loss in the course of TDS measurement preparation, namely during AVC pumping, has not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Storage of specimens at cryogenic temperatures is used to suppress hydrogen diffusivity, preventing hydrogen loss in steel specimens prior to measurements. The process described in standard BS ISO 3690 is used to store samples up to 15 days before the hydrogen measurement [19,23,24]. In order to study the hydrogen diffusivity and trapping at low temperatures, the cryogenic-TDS technique (C-TDS) was developed [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent investigations aimed at understanding the causes behind WEC related bearing failure in wind turbine gearboxes [5,[11][12][13][14][15][16][17][18][19][20]. However, the causes of WEC bearing failures remain a subject of debate [5,10,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These results not only implicate the so-called 'WEC critical oil', but also indicate that oil additives may have an influence on risk of WECs. Similarly, several other investigations used a specific oil, containing additives, to successfully promote WEC failure [1,10,21,23,27], the most recent of which is the investigation by Gould et al, where lubricant additives were systematically varied to study the effect of different additive combinations on bearing time until failure [24]. The investigation found that the lubricant containing zinc dialkyl-dithiophosphate (ZnDDP) led to WECs sooner than any other tested lubricant under the test conditions [24].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Although wind turbine gearboxes tend to fail predominately at critical bearing locations because of white structure flaking (WSF), 2 several recent studies on wind turbine gearbox rolling element bearings have shown that lubrication conditions can also have an impact on rolling contact fatigue (RCF). [21][22][23] Similarly, it has been shown elsewhere that the boundary and mixed lubrication regimes together with frictional energy should be used as key input parameters in tribological experiments that aim to reproduce actual service operating conditions that initiate WSF. [24][25][26] The high friction coefficients present at such EHD lubrication conditions are known to raise subsurface shear stresses closer to the surfaces of bearings, which possibly lead to WSF in wind turbine bearings.…”
mentioning
confidence: 99%